DAMPAK PENGARUH MOTIF DAN PENDETEKSIAN KECURANGAN TERHADAP ANTISIPASI KONSEKUENSI KECURANGAN LAPORAN KEUANGAN - Elizabethara Rusna Putri; - Tarjo; Yuni Rimawati (Master of Accounting Universitas Trunojoyo Madura, 2015)
The purpose of this study is to examine and know the impact of the effect of motives cheating on anticipation a consequence Fraudulent Financial Statement , to examine and know the impact of the effect of detection of fraud on anticipation a consequence Fraudulent Financial Statement , and to examine and know that the interaction between motives of fraud with detection of fraud in effect anticipation a consequence Fraudulent Financial Statement. The population in this research were participant of Conference Accounting Regional II at the University of Kanjuruan Malang. The selection of sample on this research conducted with random sampling techniques .The data used is primary data using a questionnaire and analyzed using analysis MANOVA data processing using SPSS version 16.0.The result of this research are (1) MANOVA of the overall result was obtained on that motive of fraud consequences affecting anticipation cheating financial reports .Detection fraud not affect anticipation a consequence Fraudulent Financial Statement. Yet there was interaction between motives of fraud with detection of fraud. (2) The result test between subject effect shows the partial evaluation significant that some anticipation a consequence fraudulent financial statement effected by a motive and interaction motives with detection of fraud and on the other hand also consequences partial evaluation anticipation Fraudulent Financial Statement show results not affected by the existence of fraud detection.